The Prevalence and Success Factor of Ibuprofen and Paracetamol Administration for Neonates with Patent Ductus Arteriosus at RSUD Dr. Soetomo - Rodia Amanata Rofiq; I Ketut Alit Utamayasa; Nurina Hasanatuludhhiyah; Arthur Pohan Kawilarang (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Four thousand neonates with Persisten Ductus Arteriosus every year in Indonesia. There are twotreatment options to treat Persistent Ductus Arteriosus, they are surgery and pharmacological therapy. Ibuprofenand paracetamol can be used as pharmacological therapy for Persistent Ductus Arteriosus with minimal sideeffects.Objective: To analyze the prevalence and success factors in giving ibuprofen and paracetamol in neonates withpersistent ductus arteriosus.Method: This research is an observational analytic research with cross-sectional method. The determination of theresearch sample uses a total sampling technique by taking all members of the population in accordance with theconditionsfrom January, 2016 to March , 2020. Bivariate analysis was perform using the Spearman rank test with95% confidence interval (α=0.05).Result: From 51 samples that met the inclusion criterias, it was found that the most criterias were male (66.67%),normal birth weight (60.78%), aterm (76.48%), moderate defect size before being administrated pharmacologicaltherapy (47.06%), pharmacological therapy using paracetamol (88.24%), atrial septal defect in the cardiaccomorbidities category (21.74%) and hyperbilirubinemia in the non-cardiac comorbidities category (13.04%). Themajority of lumen defects in neonates were closed completely after being administrated pharmacological therapy(72.55%). Statistical test results of spearman rank showed that no significant relationship between birth weightand pharmacological therapy in RSUD Dr. Soetomo. There was a significant relationship between gestation andpharmacological therapy (p = 0.000; r = -0.495; r2 = 0.237, 95% CI). There was a significant relationship between thesize of the ductus arteriosus defect before therapy and pharmacological therapy (p = 0.001; r = -0.435; r2 = 0.211,95% CI). Conclusion: The success factors in administrating ibuprofen and paracetamol for neonates with persistent ductusarteriosus in RSUD dr. Soetomo from January 1, 2016 to March 3, 2020 were affected by gestation period and sizeof the ductus arteriosus defect prior to pharmacological therapy.